2017
DOI: 10.1371/journal.pone.0174030
|View full text |Cite
|
Sign up to set email alerts
|

A maternal high-fat, high-sucrose diet has sex-specific effects on fetal glucocorticoids with little consequence for offspring metabolism and voluntary locomotor activity in mice

Abstract: Maternal overnutrition and obesity during pregnancy can have long-term effects on offspring physiology and behaviour. These developmental programming effects may be mediated by fetal exposure to glucocorticoids, which is regulated in part by placental 11β-hydroxysteroid dehydrogenase (11β-HSD) type 1 and 2. We tested whether a maternal high-fat, high-sucrose diet would alter expression of placental 11β-HSD1 and 2, thereby increasing fetal exposure to maternal glucocorticoids, with downstream effects on offspri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…Birth weight was obtained from N = 63 studies ( N = 6530 offspring), one study was included twice in meta‐analysis since they reported on two separate cohorts . In six studies, data on birth weight was not extractable .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Birth weight was obtained from N = 63 studies ( N = 6530 offspring), one study was included twice in meta‐analysis since they reported on two separate cohorts . In six studies, data on birth weight was not extractable .…”
Section: Resultsmentioning
confidence: 99%
“…Sixty‐eight studies, including N = 1980 animals, reported on offspring's glucose levels at birth until 12 months of age. One study was included twice in the meta‐analysis since they reported on two different cohorts . In five studies, we were unable to extract outcome data .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies by us and by others (Chin et al, ; Weksler‐Zangen et al, ) showed that rat pups weight did not vary between the genders up to PND 21. Hence, we did not discriminate between genders before weaning.…”
Section: Resultsmentioning
confidence: 56%